Chronology of Alcohol Dependence: Implications in Prevention - Manjunatha, Narayana (Medknow Publications, 2008)
BACKGROUND: Study of the chronology of criteria of dependence in alcohol dependence syndrome (ADS) can enable us design strategies for the prevention for ADS, which aims at reducing the occurrence of ADS. OBJECTIVE: To study the age-wise and order-wise chronologies of ICD-10 (DCR) dependence criteria in individuals with ADS. MATERIALS AND METHODS: Consecutively admitted and consenting inpatients with ICD-10 (DCR) diagnosis of ADS were evaluated in a structured interview after detoxification using Semi-Structured Assessment for the Genetics of Alcoholism (SSAGA)-II. RESULTS: The total sample size was 81. The mean ages at the first onset of alcohol use, development of the first criterion and International Statistical Classification of Diseases and Related Health Problems 10(th) Revision (ICD-10) dependence was 18.72 years (SD, 6.84), 24.33 years (SD, 9.21) and 27.51 years (SD, 9.28), respectively. In age-wise chronology, tolerance, loss of control and craving were present in 97.53%, 80.24% and 79%, respectively, of our study sample. In order-wise chronology, either craving (16%) or tolerance (71.6%) was present as the first criterion and the presence of craving (16%), tolerance (21%) or loss of control (18.5%) was observed in the first criterion in 55.5% of the subjects. CONCLUSIONS: Knowledge of chronology, its frequencies and time duration between various milestones in the development of the dependence criteria may enable the selection of the target population at an early stage. The pattern of development of dependence may provide us with an opportunity for interventions to reduce the incidence of ADS, as a step toward primary prevention. Adequate training of the primary care personnel and early psychiatric referral may help in the reduction in the incidence of ADS.